Psychiatric Symptoms in Oncological Patients at Nuclear Medicine Department - İlce, Huri Tilla and Vargol, Sezen Elhan and Halis, Hatice and Yazici, Esra (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: In the process of PET/CT scanning, patients go through a general evaluation while their medical history is being taken, but it is often overlooked that these patients should be evaluated not only biologically but also bio psychosocially. Psychiatric symptom profiles and help-seeking behaviours of cancer patients were examined in this study. Methods: Cancer patients presented to nuclear medicine clinic filled out sociodemographic data form, psychiatric admission evaluation form, Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Symptom Checklist-90 (SCL-90) form for psychiatric symptom screening. Results: In this study 27.8% of the patients had a Beck Depression score ≥18 and were in the risk group for depression, 31.7% of the patients experienced moderate or severe anxiety symptoms. Beck Depression Total and Beck Anxiety Total values were found significantly higher in women than in men. Only 10,2% of the cancer patients reported that they sought psychiatric help in the last 6 months. Among the patients who were risky for depression according to BDI only 25% had been receiving psychiatric help and in among the patients who were risky for anxiety according to BAI only %26.9 had been receiving psychiatric help Conclusion: Nuclear Medicine physicians’ interest in psychiatric symptoms and help-seeking behaviors of cancer patients referred to Nuclear Medicine Clinics is very important in terms of psycho-oncology.